Redesigning The Esp Course For Architecture Major At Multimedia Nusantara University - Emanuella Christine Natalia Mau (Universitas Cokroaminoto Palopo, 2025)
The article discusses the redesign of the English for Specific Purposes (ESP) course, employing a conceptual framework to elaborate on and design effective teaching strategies and materials for Architecture Major Students. This approach addresses challenges in English Language Teaching (ELT) for non-English department students at Multimedia Nusantara University. The redesign utilizes Evidence-Centered Design (ECD) and Task-Based Language Teaching (TBLT) within a Flipped Classroom course structure to enhance the ESP course.